Rules of origin across African regional trading agreements: A landscape with measures to address challenges at harmonization - Julien Gourdon; Dzmitry Kniahin; Jaime De Melo; Mondher Mimouni (Journal of African Trade, 2021)
To become operational, the African Continental Free Trade Area (AfCFTA) must harmonize Rules of Origin (ROO) across Africa's Preferential Trade Agreements (PTAs) along two dimensions: regime-wide rules and product-specific rules. This paper describes and evaluates these ROO across the major multiple-membership PTAs engaged in these harmonization negotiations. These PTAs include: The Agadir Agreement, the Greater Arab Free Trade Area, the Common Market for East and South Africa, the East Africa Community, the Economic Community of West African States and the Southern African Development Community. To this list we add available regime-wide information on two Free-trade-areas (FTAs): the Tripartite FTA and the AfCFTA. The paper makes three contributions. It provides the first comprehensive description of regime-wide rules (RWR) and productspecific rules (PSR) separately across the main African PTAs. This landscape is built up from the complementary work based on the rules of origin facilitator1 that has categorized the 850 textually distinct PSR across six selected African PTAs. Second, the paper proposes metrics to evaluate differences along three dimensions: (i) wording-based text analysis; (ii) distance measures to indicate regulatory overlap; (iii) ordinal index to measure restrictiveness based of RWR and PSR. Third, it proposes a dashboard for negotiators incorporating the classifications and measures developed in the text along with other indicators.
Keywords: F1; F14; F15; 330; AfCFTA; rules of origin; product-specific rules of origin; regime-wide rules of origin; compliance costs